2022
DOI: 10.1186/s13071-021-05138-x
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution melting analysis identifies reservoir hosts of zoonotic Leishmania parasites in Tunisia

Abstract: Background Leishmaniasis is endemic in Tunisia and presents with different clinical forms, caused by the species Leishmania infantum, Leishmania major, and Leishmania tropica. The life cycle of Leishmania is complex and involves several phlebotomine sand fly vectors and mammalian reservoir hosts. The aim of this work is the development and evaluation of a high-resolution melting PCR (PCR-HRM) tool to detect and identify Leishmania parasites in wild and domestic hosts, constituting confirmed (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
1
0
0
Order By: Relevance
“…Moreover, these findings revealed that coinfections events are more prevalent than previously thought. Coinfection is not limited solely to humans, as indicated by our current study and previous research [ 16 , 17 , 34 , 80 , 81 ], but is also evident in sand fly vectors [ 16 , 17 , 82 ] and reservoirs [ 16 , 17 , 83 , 84 ]. The identification of these coinfection events holds paramount importance in comprehending the intricate eco-epidemiology of the disease.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, these findings revealed that coinfections events are more prevalent than previously thought. Coinfection is not limited solely to humans, as indicated by our current study and previous research [ 16 , 17 , 34 , 80 , 81 ], but is also evident in sand fly vectors [ 16 , 17 , 82 ] and reservoirs [ 16 , 17 , 83 , 84 ]. The identification of these coinfection events holds paramount importance in comprehending the intricate eco-epidemiology of the disease.…”
Section: Discussionsupporting
confidence: 81%